Selective liquid-chromatographic determination of native fluorescent biogenic amines in human urine based on fluorous derivatization - Sakaguchi, Yohei; Yoshida, Hideyuki; Hayama, Tadashi; Itoyama, Miki; Todoroki, Kenichiro; Yamaguchi, Masatoshi; Nohta, Hitoshi (Journal of Chromatography A, 2011)
A liquid chromatographic (LC) derivatization method for simple and selective determination of catecholamines and indoleamines in human urine has been developed. This method uses “fluorous interaction” in which perfluoroalkyl compounds show affinity with each other. The amino groups of native fluorescent analytes are precolumn derivatized with a non-fluorescent fluorous isocyanate, 2-(perfluorooctyl)ethyl isocyanate, and the fluorous-labeled analytes are retained in the fluorous LC column, whereas underivatized substances are not. Only the retained fluorous-fluorescent analytes are detected fluorometrically at appropriate retention times, and retained amines without fluorophores are not detected. In this study, 3,4-dihydroxyphenylalanine, dopamine, norepinephrine, epinephrine, and metanephrine were used as the representative of catecholamines. Tryptophan, 5-hydroxytryptophan, and 5-hydroxytryptamine were used as the representative indoleamines. This method was applied to determine eight biogenic amines in urine from healthy humans. The fluorous-labeled amines could be separated by fluorous LC column under conditions of isocratic elution within 35 min and simultaneously determined without interference from contaminants in biological samples. The detection limits for eight biogenic amines were 31–640 fmol on column. Calibration curves of them were linear over the range of at least 10–100 nmol/mL urine ( r 2 > 0.9989) with good repeatability.